2005
DOI: 10.1016/j.trd.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation or causality between the built environment and travel behavior? Evidence from Northern California

Abstract: The sprawling patterns of land development common to metropolitan areas of the US have been blamed for high levels of automobile travel, and thus for air quality problems. In response, smart growth programs-designed to counter sprawl-have gained popularity in the US. Studies show that, all else equal, residents of neighborhoods with higher levels of density, land-use mix, transit accessibility, and pedestrian friendliness drive less than residents of neighborhoods with lower levels of these characteristics. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
491
1
19

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 886 publications
(584 citation statements)
references
References 9 publications
24
491
1
19
Order By: Relevance
“…Every respondent receives a score for the "pro-transit" factor, with positive and higher scores indicating a stronger positive attitude towards using transit and lower, more negative scores indicating a negative attitude towards transit. Using these factor scores, Mokhtarian and Handy have found a significant relationship between attitudes and travel behavior, sometimes a stronger relationship than with land use (Handy, Cao, and Mokhtarian 2005;Kitamura, Mokhtarian, and Laidet 1997).…”
Section: Attitudes Norms Perceived Behavioral Control and Intentionsmentioning
confidence: 99%
“…Every respondent receives a score for the "pro-transit" factor, with positive and higher scores indicating a stronger positive attitude towards using transit and lower, more negative scores indicating a negative attitude towards transit. Using these factor scores, Mokhtarian and Handy have found a significant relationship between attitudes and travel behavior, sometimes a stronger relationship than with land use (Handy, Cao, and Mokhtarian 2005;Kitamura, Mokhtarian, and Laidet 1997).…”
Section: Attitudes Norms Perceived Behavioral Control and Intentionsmentioning
confidence: 99%
“…Handy et al (2005Handy et al ( , 2006 developed three ordered probit models to investigate the unidirectional causal link from the built environment to travel behavior. After accounting for the influence of current attitudes and changes in socio-demographics, they found that changes in neighborhood characteristics consistently affected changes in these behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, they treated auto ownership as exogenous in the relationship between the built environment and driving behavior, but it was actually endogenous. Cao et al (2007) and Handy et al (2005) showed that changes in the built environment influence changes in auto ownership, which in turn affect changes in driving. In other words, auto ownership is a mediating link connecting the built environment and travel behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations